Sistem Informasi Manajemen Kos-Kosan Menggunakan Metode Content Management System Di Kota Banda Aceh - Hasridayyana, Ira; Ahmad, Lukman; Junaidi, Rahmad (Jurnal Sistem Komputer (SISKOM), 2023)
Management Information Systems (MIS) have become an integral part of modern organizations to facilitate data processing, decision making, and provision of relevant information. This research aims to design a boarding house SIM using the Content Management System (CMS) method in Banda Aceh City. A qualitative approach with descriptive methods was used to collect data from boarding house owners and boarding house users through direct interviews, as well as other data sources such as books, journals and online sources. Data collection techniques use CMS to enable dynamic management of website content without in-depth technical knowledge. The development process follows the waterfall model with stages of analysis, design, coding and testing. The result is a system that allows users to search for and book boarding houses online, and provides benefits for the author in increasing knowledge about boarding house SIMs and for boarding house owners in promoting their properties digitally.